Efficacy of Lavender Aromatherapy in Increasing Breast Milk Consumption Among Postpartum Mothers at Kertajati Health Centre - Ropiah, Opi; Tonasih, Tonasih; Mutya Sari, Vianty (Ann Publisher, 2023)
Breast milk production is a cumulative value based on what is seen and can be measured by the volume of milk a baby drinks for one day. The causes of decreased breast milk are consumption of drugs and hormonal disorders. To overcome the issue of decreased drain generation, lavender fragrance-based treatment can be done. The reason for this ponder was to decide the adequacy of giving lavender fragrance-based treatment to expand the sum of drain excretion in postpartum moms. This type of investigation is pre-experimental, with a number of pretest-posttest designs. Total sampling is a technique for sampling. The comes about appeared that the normal sum of breastfeeding time recently given fragrance-based treatment was 72.75. The minimum amount of breastfeeding in postpartum mothers is 60 cc and the maximum amount is 85 cc. After aromatherapy, the average amount of nursing in postpartum women is 100.25. Giving lavender aromatherapy is beneficial in raising milk production in postpartum moms, and it is anticipated that Kertajati Health Center in Majalengka Regency would be able to use this approach as a non-pharmacological treatment to improve milk production.